2013
DOI: 10.1088/0953-2048/26/3/035003
|View full text |Cite
|
Sign up to set email alerts
|

Proximity breakdown of hydrides in superconducting niobium cavities

Abstract: Many modern and proposed future particle accelerators rely on superconducting radio frequency cavities made of bulk niobium as primary particle accelerating structures. Such cavities suffer from the anomalous field dependence of their quality factors Q 0 . High field degradation -so-called 'high field Q-slope' -is yet unexplained even though an empirical cure is known. Here we propose a mechanism based on the presence of proximity-coupled niobium hydrides, which can explain this effect. Furthermore, the same m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 19 publications
7
63
0
Order By: Relevance
“…7,13,20 At this stage, it is not yet possible to definitively say, if it is the volume density or the size of the nanohydrides, which is affected. However, the removal of the HFQS suggests that it is likely the size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,13,20 At this stage, it is not yet possible to definitively say, if it is the volume density or the size of the nanohydrides, which is affected. However, the removal of the HFQS suggests that it is likely the size.…”
Section: Discussionmentioning
confidence: 99%
“…6 The most recent promising model is based on the formation of lossy niobium nanohydrides in the penetration depth. 7 In the past, larger non-superconducting hydrides were identified as an origin of hydrogen Q disease. 8,9 Nanohydrides may remain superconducting due to the proximity effect up to the breakdown field, which is determined by their size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion of what defects can serve as nucleation centers is still open but we think that vacancies and hydrogen-vacancies complexes are among likely candidates. 5,12 We start with the assumption that hydrogen is uniformly distributed in the sample volume, and hydride nuclei are spaced by the distance L. The schematic used for this model is shown in Fig. 11.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The effect was attributed to the formation of non-superconducting niobium hydride phases, and it was quickly found that Q disease can be "cured" and prevented by vacuum annealing at T > 600 C for several hours, presumably due to the decrease of the bulk hydrogen concentration. More recently, smaller hydrides were proposed 5,6 as a cause for another cavity limitation-a "high field Q slope," understanding of which is an area of active ongoing research.…”
Section: Introductionmentioning
confidence: 99%